2020
DOI: 10.1016/j.celrep.2020.107940
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir Inhibits SARS-CoV-2 in Human Lung Cells and Chimeric SARS-CoV Expressing the SARS-CoV-2 RNA Polymerase in Mice

Abstract: Highlights d Remdesivir binding of active site of polymerase is conserved across all human CoVs d Remdesivir inhibits SARS-CoV-2 in primary and continuous human lung cell cultures d Remdesivir potency depends on cell-type-specific metabolism to its active form d Therapeutic remdesivir reduces viral loads and improves outcomes in mice

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
519
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(607 citation statements)
references
References 58 publications
66
519
5
4
Order By: Relevance
“…This occurs by the successive action of carboxyesterases, cathepsin A and phosphoramidases [16,23]. However, this approach does not appear to provide any benefit in Vero E6 cells, a monkey kidney cell line, as shown by Pruijssers et al [24] and by our results showing the antiviral activity of RVn is greater than that of RDV.…”
Section: Discussionmentioning
confidence: 78%
“…This occurs by the successive action of carboxyesterases, cathepsin A and phosphoramidases [16,23]. However, this approach does not appear to provide any benefit in Vero E6 cells, a monkey kidney cell line, as shown by Pruijssers et al [24] and by our results showing the antiviral activity of RVn is greater than that of RDV.…”
Section: Discussionmentioning
confidence: 78%
“…Next, compounds were tested in Vero cells infected with SARS‐CoV‐2 at a multiplicity‐of‐infection (MOI) of 0.1 (Fig A), resulting in death of ~ 50% of the cell population. Remdesivir (RDV) (preprint: Pruijssers et al , ; Wang et al , ), the only available drug approved for treatment of COVID‐19, was used at 12.5 μM concentration (Choy et al , ), leading to a ~ 90% reversal of the SARS‐CoV‐2 induced CPE. Hydroxychloroquine (HCQ), at 10 μM (Yao et al , ), rescued CPE also by ~ 90% (Figs B, and EV6C and D).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we found that SARS-CoV-2 replication could be inhibited by SFV at high concentration, not only in hepatoma cells – but also in Calu-3 type II pneumocytes. Interestingly, RDV, which shares structural characteristics with SFV, such as to be converted from the ProTide/prodrug to active metabolite, is active in the respiratory tract[39]. Moreover, there is a body of evidence suggesting that the ProTide phospharamidate protections would be dispensable from RDV in respiratory cells because the nucleoside analog, GS-441524, is active against human and feline CoV [3941].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RDV, which shares structural characteristics with SFV, such as to be converted from the ProTide/prodrug to active metabolite, is active in the respiratory tract[39]. Moreover, there is a body of evidence suggesting that the ProTide phospharamidate protections would be dispensable from RDV in respiratory cells because the nucleoside analog, GS-441524, is active against human and feline CoV [3941]. Since there are open questions on the efficiency in which respiratory cells convert nucleosides to nucleotides, the nucleoside version of SFV (GS-331007) was tested against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%